PMC-Labeling of Certain Classes of Graphs - R Ponraj; S Prabhu; A M S Ramasamy (Journal of Fundamental Mathematics and Applications (JFMA), 2025)
In this paper, we investigate the PMC-labeling behavior of some new graphs such as the double fan graph, triple fan graph, $m$--enriched fan graph,  C_{n}--snake, stripe blade graph, G_{n}, Sf_{n} + K_{1}, armed helm graph, alternate armed helm graph and spectrum graph.